HISTOPATHOLOGICAL IMAGE OF THE NUMBER OF NEURONS IN THE BRAIN OF MICE (MUS MUSCULUS) INDUCED BY LEAD HEAVY METAL - Herera Rahajeng; Eka Sri Haryati; Ichwan Baihaki; Niken Rahmah Ghanny; Afifa Radhina; Assyafiya Salwa; Fransiskus Samuel Renaldi (Journal of World Future Medicine, Health and Nursing, 2026)
Lead is a known heavy metal from human history to date for various uses, abuses and toxicities. Lead poisoning has been recognized as one of the most serious environmental health issues worldwide, especially children living in developing countries. Lead can damage or affect the organs of the body, among others, the nervous system, kidneys, reproductive system, and heart, as well as disturbances in the brain so that intellectual and mental disorders in the brain. This study aims to see the effect of lead on the number of neurons in the hippocampus in mice experimental animals. The mice used amounted to 10 tails and divided into two for the control group and the treatment group. The control group, each of which was 5 tails, was then given unbleached drinking water while the treatment group was given drinking water mixed with acetate with concentration of 1000ppm for 17 days in adlibitum. The observations were taken from each of the 5 fields of view on each preparation with a magnification of 40x. The calculation of the number of neuron cells is then analyzed descriptive statistics and different test. The result showed that control group with mean ± SD were 127,6 ± 7,9, and for treatment group that was 80,0 ± 20,9. T independent test result showed p = 0,001 (p <0,05) which means that there was a significant difference between control and treatment group. The conclusion of this research is the existence of neuron cell damage in mice that get treatment. By showing the number of neurons less than the control mice. Suggestion to develop this research hence need to continue research to find neuro protector compound specially from lead work in brain.